Relationship between Serum Uric Acid and Lipid Profiles in Thai Adults (Indian Journal of Public Health Research & Development, 2020)
Although the link between serum uric acid, including hyperuricemia and metabolic syndrome had beenreported, the relationship of lipid profiles with serum uric acid remains not comprehensively assessed inThai adults. This current study was performed to examine the relation between serum uric acid and lipidprofiles in Thai adults. A total of 192 blood samples were collected from Thai adults aged 20 years and over(men, n = 67 and women, n = 125). We analyzed serum uric acid levels and serum lipid profiles, includingserum total cholesterol, triglycerides, low-density lipoprotein and high-density lipoprotein. Multiple linearregression analysis was used to evaluate the relationship between serum uric acid and lipid profiles. Ourresults found that triglycerides and total cholesterol was linearly related with serum uric acid levels (0.404,95% CI, 0.578, 95% CI 0.164-0.993, respectively). Meanwhile an inverse relation was observed betweenserum uric acid levels and high-density lipoprotein (-0.042, 95% CI -0.015 - -0.067).This study suggested that triglycerides, total cholesterol and obesity had a significant linear association withserum uric acid levels, whereas serum HDL cholesterol levels are significantly inversely associated.Theearly prevention of obesity and dyslipidemia can reduce the incidence of associated hyperuricemia and goutamong Thai adults
Keywords: Serum uric acid, Lipid Profiles, Total cholesterol, Triglycerides, Low density lipoprotein, High density lipoprotein